Effects of Dietary Ginsenoside Rg1 Supplementation on Growth Performance, Gut Health, and Serum Immunity in Broiler Chickens - Song, Zehe; Xie, Kaihuan; Zhang, Yunlu; Xie, Qian; He, Xi; Zhang, Haihan (Frontiers in Nutrition, 2021)
The restriction and forbidden of antibiotics in farm animal feed caused the seeking of promising substituents with closed function of antibiotics to promote the growth and maintain the health for livestock and poultry. Ginsenoside Rg1, which is the most effective bioactive component in ginseng, has been reported to have great potentials to improve the anti-inflammatory and anti-oxidative status of animals. In this study, we designed an experiments with 360 Chinese indigenous broiler chickens divided into five groups, which were control group fed with basal diet, antibiotic group fed with basal diet + 300 mg/kg 15% chlortetracycline, Rg1 supplementation groups fed with basal diet + 100, 200 and 300 mg/kg ginsenoside Rg1, respectively. The growth performance, immune function and intestinal health of birds were examined at early (day 1-28) and late (day 29-51) stages. Our results showed that dietary supplementation of 300 mg/kg ginsenoside Rg1 significantly improved the growth performance for broilers, particularly at the late stage, including the increase of final body weight and decrease of feed conversion ratio. Additionally, the integrity of intestinal morphology and tight junction, and the secretion of sIgA in intestine were enhanced by the supplementation of Rg1 in chicken diet. However, the little effects were observed in the change of intestinal microbiota with the supplementation of Rg1. The immune organ index showed that the weight of thymus, spleen and bursa was significantly increased at the early stage in ginsenoside Rg1 supplementation groups, which might be caused by the ability of ginsenoside Rg1 to suppress the secretion of pro-inflammatory cytokine and stimulate the production of anti-inflammatory cytokines, complement system, and immunoglobubins. Our findings might demonstrate that ginsenoside Rg1 could serve as a promising antibiotic alternative to improve the growth performance and gut health for broiler chicken mainly through its amelioration of the inflammatory and oxidative activities.